2010
DOI: 10.1186/1471-213x-10-52
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and migration of trunk neural crest cells in a snake, the California Kingsnake (Lampropeltis getula californiae)

Abstract: BackgroundThe neural crest is a group of multipotent cells that emerges after an epithelial-to-mesenchymal transition from the dorsal neural tube early during development. These cells then migrate throughout the embryo, giving rise to a wide variety derivatives including the peripheral nervous system, craniofacial skeleton, pigment cells, and endocrine organs. While much is known about neural crest cells in mammals, birds, amphibians and fish, relatively little is known about their development in non-avian rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
51
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 43 publications
12
51
3
Order By: Relevance
“…Nevertheless, chicken is not the only organisms whose neural crest cells express HNK1 epitope. Other squamata, like turtles, snakes and crocodile neural crest are well labeled with HNK1 (Cebra-Thomas et al, 2007; Kundrat, 2008; Reyes et al, 2010). Although the best universal marker for neural crest cells is the transcription factor Sox10 (Cheng et al, 2000; Sauka-Spengler and Bronner-Fraser, 2006), HNK1 as shown above is a reliable and easy marker to use when studying neural crest cells, thus our present approach following on a well-established method by crest researchers and as a practical way to study in detail the migratory pattern of these cells in the chicken embryo.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, chicken is not the only organisms whose neural crest cells express HNK1 epitope. Other squamata, like turtles, snakes and crocodile neural crest are well labeled with HNK1 (Cebra-Thomas et al, 2007; Kundrat, 2008; Reyes et al, 2010). Although the best universal marker for neural crest cells is the transcription factor Sox10 (Cheng et al, 2000; Sauka-Spengler and Bronner-Fraser, 2006), HNK1 as shown above is a reliable and easy marker to use when studying neural crest cells, thus our present approach following on a well-established method by crest researchers and as a practical way to study in detail the migratory pattern of these cells in the chicken embryo.…”
Section: Resultsmentioning
confidence: 99%
“…Although melanoblasts in mammals and birds are known to migrate mainly via the dorsolateral route from the neural crest, those in lower vertebrates are often observed to travel through the ventral route (Collazo et al 1993;Eisen 1994, 1996;Kelsh 2004;Akiyama et al 2006a;Tomlinson et al 2009;Reyes et al 2010). Investigation of Silky chickens could also provide significant clues to recognize the evolutionary divergence of melanoblast migration.…”
mentioning
confidence: 99%
“…In addition to observing DiI cells in segmented streams along the lateral line in the trunk, we also observed a group of DiI cells at the tail end migrating as a sheet and a smaller number as a stream migrating rostrally on the ventral portion of the tail. Although we do not know the ultimate destiny of these “returning” populations, the same neural crest migratory pattern has been observed in fish (Collazo et al, ) and amphibians (Collazo et al, ) but not in reptiles (Reyes et al, ) or mammals (Kuhlbrodt et al, ). This suggests that the migratory path became lost in nonaquatic gnathostomes.…”
Section: Discussionmentioning
confidence: 54%
“…Past studies have shown that Sox8 and Sox9 sequences are highly conserved among fish, amphibians, reptiles, and mammals. Even more striking than sequence conservation, however, is the conserved patterns of migration and expression in vertebrate neural crest cells and their derivatives (Horigome et al, ; Bell et al, ; Sauka‐Spengler and Bronner‐Fraser, b; Guth et al, ; Reyes et al, ). This was especially remarkable in the trunk regions of C. punctatum embryos, because segmental migration through the rostral portion of the somites is practically undistinguishable from that of other vertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation